2016
DOI: 10.1038/srep29000
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Streptococcus urinary tract infection depends on bacterial strain and β-hemolysin/cytolysin that mediates cytotoxicity, cytokine synthesis, inflammation and virulence

Abstract: Streptococcus agalactiae can cause urinary tract infection (UTI) including cystitis and asymptomatic bacteriuria (ABU). The early host-pathogen interactions that occur during S. agalactiae UTI and subsequent mechanisms of disease pathogenesis are poorly defined. Here, we define the early interactions between human bladder urothelial cells, monocyte-derived macrophages, and mouse bladder using uropathogenic S. agalactiae (UPSA) 807 and ABU-causing S. agalactiae (ABSA) 834 strains. UPSA 807 adhered, invaded and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 61 publications
5
47
0
Order By: Relevance
“…Interestingly, those down stream of pyroptotic signaling (e.g. IL-6, IGF1, IL-1ß) are dependent on Ogg1 expression and documented to be consequential to the bladder pathology373839. Future studies could test if long-term prophylactic treatment with HDAC inhibitors following CPX/mesna treatment schedule could reduce the rates of hemorrhagic cystitis in this highly susceptible population.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, those down stream of pyroptotic signaling (e.g. IL-6, IGF1, IL-1ß) are dependent on Ogg1 expression and documented to be consequential to the bladder pathology373839. Future studies could test if long-term prophylactic treatment with HDAC inhibitors following CPX/mesna treatment schedule could reduce the rates of hemorrhagic cystitis in this highly susceptible population.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the early steps in pathogenesis of S . agalactiae UTI have been reported related to strain differences [14]; some of these differences may relate to virulence factors such as the hemolysin [14, 57], or capsule, the sialic acids of which enhance the survival of S . agalactiae in the urinary tract [13] and augment the ability of E .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that the pathogenesis of S . agalactiae UTI encompasses binding of the bacteria to the bladder [11, 12], cytotoxicity in urothelial cells, and elicitation of pro- and anti-inflammatory cytokine and chemokine responses [13, 14], as well as growth of some ABU-causing S . agalactiae in human urine that may affect persistence [15].…”
Section: Introductionmentioning
confidence: 99%
“…For immune profiling of mouse bladders, tissues were collected and homogenized in protease inhibitor as described in ref. 32. Supernatants were frozen at 280°C until assay.…”
Section: Cytokine Analysis By Elisa and Multiplex Assaysmentioning
confidence: 99%